Going mobile with primary care: smartphone-telemedicine for asthma management in young urban adults (TEAMS). (2nd January 2022) - Mammen, Jennifer R.; Schoonmaker, Judith D.; Java, James; Halterman, Jill; Berliant, Marc N.; Crowley, Amber; Reznik, Marina; Feldman, Jonathan M.; Fortuna, Robert J.; Frey, Sean M.; Turgeon, Kelsey; Philibert, Ashley; et al.
Abstract: Background: The majority of adults with persistent asthma have chronically uncontrolled disease and interventions to improve outcomes are needed. We evaluated the efficacy, feasibility, and acceptability of a multi-component smartphone-telemedicine program (TEAMS) to deliver asthma care remotely, support provider adherence to asthma management guidelines, and improve patient outcomes. Methods: TEAMS utilized: (1) remote symptom monitoring, (2) nurse-led smartphone-telemedicine with self-management training for patients, and (3) Electronic medical record-based clinical decision support software. Adults aged 18-44 ( N  = 33) and primary care providers ( N  = 4) were recruited from a safety-net practice in Upstate New York. Asthma control, quality of life, and FEV1 were measured at 0, 3 and 6 months. Acceptability was assessed via survey and end-of-study interviews. Paired t-test and mixed effects modeling were used to evaluate the effect of the intervention on asthma outcomes. Results: At baseline, 80% of participants had uncontrolled asthma. By 6-months, 80% classified as well-controlled. Improvements in control and quality of life were large ( d  = 1.955, d  = 1.579). FEV%pred increased 4.2% ( d  = 1.687) with the greatest gain in males, smokers, and lower educational status. Provider adherence to national guidelines increased from 43.3% to 86.7% (CI = 22.11-64.55) and patient adherence to medication increased from 45.58% to 85.29% (CI = 14.79-64.62). Acceptability was 95.7%; In follow up interviews, 29/30 patients and all providers indicated TEAMS worked better than usual care, supported effective self-management, and reduced symptoms over time, which led to greater self-efficacy and motivation to manage asthma. Discussion: Based on these findings, we conclude that smartphone telemedicine could substantially improve clinical asthma management, adherence to guidelines, and patient outcomes.